The parametric study of electromagnetic for energy harvester - Khairul Bariah, Mashid (2012)
Nowadays, the demand of renewable energy is dramatically increased. From the waste of vibration that produced from mechanical system or human being movement, Electromagnetic Energy Harvester (EEH) can generate electricity. EEH is proposed in this thesis which generates electricity from mechanical energy when embedded in a vibration medium. The objectives of the thesis are to analyze the generated voltage and to investigate the performance of the vibration electromagnetic energy harvester for different number of turn coil. A one dimension model was built based on the principle of a spring mass system to convert energy of vibration into electrical energy. It has been designed and fabricated, in which it consists of a permanent magnet Neodymium Iron Boron (NdFeB), a copper coil, a spring and a plastic bottle to turn coil. The minigenerator is made from a coil of wire (about 400-1200 turns) wound around the outside of a plastic 25mm diameter of bottle. The two coil ends are connected to PicosCope software. A magnet is then placed in the bottle with spring where the spring was assembled with the polystyrene base. An EEH was tested by excite the shaker based on the setup of shaker. Because of the resonant frequency, minigenerator generated voltage and directly stores the voltage in the circuit to generate electricity. Analysis predicts that the generated voltage is proportional to the number of turn. As expected, results show that the output voltage increase with increasing number of turns with 74.96033 mV at 100 Hz, 107.6059 mV at 100 Hz and 120.4737 mV at 100 Hz being generated from the 400, 800 and 1200 turn coils respectively. Moreover, to maximize voltage generation, the magnet size and number of turn coil should be as large as possible. Application of EEH is for fabricating Microelectromechanical system (MEMS). MEMS is the integration of mechanical elements, sensor and electronics on a common substrate through the utilization of microfabrication technology (microtechnology).